Media House Counting Untuk Meningkatkan Kemampuan Matematika Anak Usia Dini - Ina Aqidatul Wahidah; Jazariyah; Yayu Mega Purnamasari (Journal Ashil: Jurnal Pendidikan Anak Usia Dini, 2024)
This research is based on problems in the field, some children have not mastered children's mathematical skills such as recognizing number shapes, recognizing geometry, matching, and differentiating. This is because when learning takes place the teacher only conveys it using his fingers, writing, and simple number cards. According to STPPA, children aged 3-4 years should already know the concept of numbers and geometric shapes. Therefore, stimulation is needed to improve basic mathematical skills for early childhood, namely House Counting media. This research uses the RnD (Research And Development) Borg And Gall model through 5 stages. Products have been developed through a trial process by media experts and material experts to determine the suitability of the product. This research was conducted at RA Miftahul Falaah, Majalengka Regency, group A2 with 16 children.This data collection technique uses questionnaires, interviews, and observation. The questionnaire is used to determine the suitability of House Counting media. Interviews were conducted to obtain research data and also to see the extent to which House Counting media is effective for media children in improving their mathematical abilities. Observation is used to observe the learning process in group A2 RA Miftahul Falaah. Data analysis in this study used descriptive qualitative with percentage calculations.The results of observations and research that have been carried out show that House Counting media can improve basic mathematics skills in class A2 RA Miftahul Falaah Majelengka Regency